Effectiveness of self management techniques to reduce truant students in middle school - Latifah, Leny (Universitas Negeri Padang, 2019)
Truancy is an undisciplined behavior in the form of absence from learning and is included in one form of student misbehavior. If it is not immediately handled it can have a bad impact and become a habit that is attached to students. Self management technique is one of the behavioral development techniques through certain strategies that are carried out consistently to direct people to a positive change. The purpose of this study was to decide the effectiveness of self management techniques to cut truant behavior. The research subjects were 7th grade VIII students of Muhammadiyah Middle School 4 Singosari Malang. This research is a Quasi Experiment research using the pattern of pre-test and post-test. The instrument used is the scale of truant behavior, experimental guidelines, and observation guidelines. The results showed that the score of truant pre-test behavior was 31.2 (high class), while the post-test results showed a score of 17 (medium class). And based on the results of the Wilcoxon test obtained a significance of 0.018 < 0.05 means that the effective self-management technique to cut truancy behavior